2007
DOI: 10.1002/hbm.20454
|View full text |Cite
|
Sign up to set email alerts
|

The neural bases of attentive reading

Abstract: Recent studies have suggested that attention facilitates the formation of synchronous neural assemblies in the gamma range (>40 Hz) to amplify behaviorally relevant signals. Whether this mechanism is general or confined to sensory cortices is still a matter of debate, since there is little evidence of a direct link between attention and increased gamma synchronization in high-level brain regions. We recorded the intracerebral EEG of 10 epileptic patients while manipulating their attention during reading, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 52 publications
4
26
0
Order By: Relevance
“…Also, when possible, an additional caution is to only report observations that are reproducible across several patients with different types of epileptogenic networks and anticonvulsant medication [Fell et al, 2002;Halgren et al, 1994]. Nevertheless, an important body of iEEG research provides evidence that such issues can indeed be overcome to an extent that warrants the physiological significance of the physiological insights and novel hypotheses drawn from the data [Axmacher et al, 2008b;Brovelli et al, 2005;Canolty et al, 2006;Crone et al, 1998aCrone et al, , 2006Fell et al, 2002;Jung et al, 2008;Lachaux et al, 2003Lachaux et al, , 2005Lachaux et al, , 2006aLakatos et al, 2008;Mainy et al, 2007].…”
Section: Strengths and Limitations Of Ieeg Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, when possible, an additional caution is to only report observations that are reproducible across several patients with different types of epileptogenic networks and anticonvulsant medication [Fell et al, 2002;Halgren et al, 1994]. Nevertheless, an important body of iEEG research provides evidence that such issues can indeed be overcome to an extent that warrants the physiological significance of the physiological insights and novel hypotheses drawn from the data [Axmacher et al, 2008b;Brovelli et al, 2005;Canolty et al, 2006;Crone et al, 1998aCrone et al, , 2006Fell et al, 2002;Jung et al, 2008;Lachaux et al, 2003Lachaux et al, , 2005Lachaux et al, , 2006aLakatos et al, 2008;Mainy et al, 2007].…”
Section: Strengths and Limitations Of Ieeg Researchmentioning
confidence: 99%
“…4. Generalization: large-scale networks exhibiting GBRs have been found in a large variety of cognitive tasks involving working memory [Axmacher et al, 2008b;Howard et al, 2003;Mainy et al, 2008], declarative memory [Axmacher et al, 2008a;Fell et al, 2001Fell et al, , 2002Fell et al, , 2008Sederberg et al, 2007], reading [Mainy [Crone et al, 2001b], attention [Brovelli et al, 2005;Jung et al, 2008;Ray et al, 2008], visual Tanji et al, 2005], auditory [Bidet-Caulet and Bertrand, 2005;Crone et al, 2001a;Edwards et al, 2005], somatosensory [Aoki et al, 1999] and olfactory perception [Jung et al, 2006], motor processes [Crone et al, 1998a;Lachaux et al, 2006].…”
Section: Gamma-band Activity Modulations: a Robust Correlate Of Localmentioning
confidence: 99%
“…Measures of directed cortical information flow between sources of gamma-band activity (Supp et al, 2007) can also reveal much about the particular ways in which different brain regions interact within the perceptual and attentional networks. These measures could be particularly useful in determining the dynamics of occasionally reported induced GBA decreases relative to baseline - Lachaux et al (2005) observed that concurrently with the activation of higher-level visual areas, V1 gamma synchrony decreases and Jung et al (2008) observed decreases in ventral lateral prefrontal cortex for attended words concurrently with persistent enhancements in posterior areas. The role of these desynchronisations is not fully understood but it is assumed that they are likely to reflect the supression of processing in task-irrelevant brain regions.…”
Section: Future Directionsmentioning
confidence: 99%
“…This potentially mitigates some inflammatory burden on the brain. ECoG signals have been found to encode information about arm and hand movements (Leuthardt et al, 2004; Schalk et al, 2007; Crone et al, 1998; Miller et al, 2007; Pistohl et al, 2008; Wang et al, 2009; Kubánek et al, 2009; Ball et al, 2009; Miller et al, 2009; Chao et al, 2010; Acharya et al, 2010; Degenhart et al, 2011a; Shimoda et al, 2012; Chestek et al, 2013; Nakanishi et al, 2013), as well as auditory (Edwards et al, 2005; Trautner et al, 2006), visual (Lachaux et al, 2005), language (Crone et al, 2001; Mainy et al, 2007; Kellis et al, 2010; Wang et al; 2011, Pei et al, 2011), and attentional processes (Tallon-Baudry et al, 2005; Jung et al, 2008; Ray et al, 2008). Encouraged by these findings, researchers have begun to investigate ECoG as a potential source of control signals for BMI devices.…”
Section: Introductionmentioning
confidence: 99%